The Implementation of Asean Corporate Governance Scorecard on the Consumer Goods Industry: The Case of PT Unilever Indonesia Tbk. and PT Indofood Sukses Makmur Tbk. - Ilyasa, Raihan; Nurkholis, Nurkholis (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
Global economic outlook is increasingly worrying due to war, crisis and pandemic. During globalization, several countries are integrated to compete to develop and formulate economic areas that can compete and have selling points in the world market. ASEAN then formed a forum called the ASEAN Capital Market Forum (ACMF). In this forum, the ASEAN Corporate Governance Scorecard (ACGS) was created with the hope that it could be a solution to implementing Good Corporate Governance practices and increasing information transparency to the public. This research aims to analyze the implementation of the ACGS criteria in the two consumer goods companies that is included in the 50 companies with the largest capitalization in Indonesia, namely PT Unilever Indonesia Tbk. and PT Indofood Sukses Makmur Tbk. This research uses a qualitative method. The data analysis technique used is document content review. The data analysis procedure was carried out by classifying data and calculating weights using formulas for knowing the condition of ACGS implementation in each company. The result shows that implementation of the ASEAN Corporate Governance Scorecard which has been carried out at PT Unilever Indonesia Tbk. acquires a 80.7 score, while at PT Indofood Sukses Makmur Tbk. acquires a 62.6 score.